Overseas dispersal of Hyperolius reed frogs from Central Africa to the oceanic islands of São Tomé and Príncipe. (20th September 2014) - Bell, Rayna C.; Drewes, Robert C.; Channing, Alan; Gvoždík, Václav; Kielgast, Jos; Lötters, Stefan; Stuart, Bryan L.; Zamudio, Kelly R.; Emerson, Brent
Abstract Aim To infer the colonization history of reed frog species endemic to the oceanic islands of São Tomé and Príncipe, Hyperolius molleri and H. thomensis, we quantified phylogeographical structure in the closely related H. cinnamomeoventris species complex, which is broadly distributed across continental Central Africa. Location The Lower Guineo‐Congolian Forest and the Gulf of Guinea islands of São Tomé and Príncipe, Central Africa. Methods We combined gene and species tree analyses to investigate diversity and divergence among H. cinnamomeoventris populations, to identify the most likely dispersal route to the islands, and to infer the order in which the islands were colonized. One of the endemics (H. molleri) is distributed on both islands and we quantified genetic divergence between populations. Results We recovered three clades in H. cinnamomeoventris corresponding to West‐Central, North/East‐Central and South‐Central Africa. The island endemics form a monophyletic group most closely related to the West‐Central African H. cinnamomeoventris clade. Populations of H. molleri on São Tomé and Príncipe are reciprocally monophyletic at mitochondrial loci but nuclear gene trees do not support this divergence. Main conclusions Genetic structure in the H. cinnamomeoventris species complex coincides with biogeographical barriers identified in previous studies of Central African rain forest taxa. Individual gene tree and species tree analyses support a single dispersal event from the Ogooué or Congo river basins (West‐Central Africa) to the island of São Tomé, with subsequent divergence within São Tomé and dispersal to Príncipe.